Evaluating the Relationship Between CA15.3 Levels and Key Clinical Factors in Breast Cancer Patients of North East India - Das, Sawmik; Sarma, Anupam; Rai, Avdhesh Kumar; Bhuyan, Niharika; Sharma, Ratnadeep (Asian Pacific Journal of Cancer Care, 2026)
Introduction: Breast cancer is the most common malignancy in women worldwide, with early detection crucial for improving prognosis and survival rates. Aims and objectives: This study aims to evaluate the association between serum CA15.3 levels and the expression of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (Her2/neu) in breast cancer patients. Materials and Methods: Venous blood samples from 302 histologically confirmed breast cancer patients were analyzed. Serum CA15.3 levels were measured using an automatic chemiluminescence immunoassay system. Statistical analyses were conducted to assess the correlation between CA15.3 levels and hormone receptors in both bivariate and multivariate setups. Results: Results showed that older patients (age > 48) were over three times more likely to have elevated CA15.3 levels (OR: 3.27, 95% CI: 1.18 to 9.63). A significant association was also found between Her2/neu status and CA15.3 levels, with positive Her2/neu patients more likely to have elevated CA15.3. ER and PR statuses were similarly associated with higher CA15.3 levels, highlighting the role of hormonal factors in breast cancer. However, tumour grade did not significantly impact CA15.3 levels. The ROC curve analysis revealed moderate discriminatory power with an AUC of 0.679, indicating that the model correctly classifies approximately 67.9% of cases. The optimal threshold for predicting elevated CA15.3 levels was 0.507, yielding a sensitivity of 0.479 and specificity of 0.859. Conclusion: In conclusion, CA15.3 levels in breast cancer patients are significantly influenced by ER, PR, and Her2/neu status, as well as age.